EKSPERIMENTASI MODEL PENEMUAN TERBIMBING DAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA POKOK BAHASAN TRIGONOMETRI DITINJAU DARI KREATIVITAS SISWA SMA SE-KOTA SALATIGA TAHUN PELAJARAN 2013/2014 - Kristin Yulianti; Mardiyana Mardiyana; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of the research were to know: (1) which learning models - discovery learning, problem based learning and direct learning model - that will give the best learning mathematics result; (2) which level of students creativity- high, medium, or low- that will give te best mathematics learning result; (3) which learning models - discovery learning, problem based learning and direct learning model - that will give the best learning mathematics result in each creativity categories; (4) which level of students creativity- high, medium, or low- that will give the best mathematics learning result in each learning models. The research used a quasi-experimental designed by using two-way analysis of variance with unequal cell sizes. The population of this research are all X grade students of Senior High School in Salatiga 2013/2014. The sampling technique being used in this research was stratified cluster random sampling. The results show as follows. (1) Mathematics learning achievement using guided discovery model and problem based model show similar result which is better than using direct learning model. (2) Students with high level of creativity show better learning achievement than those of low level creativity. Students with high and medium level of creativity show the same learning achievement. Students with medium and low level of creativity show the same learning achievement. (3) On students with high level of creativity, guided discovery and problem based learning models show the same result, and guided discovery learning model results in better achievement compares to direct learning model. Problem based and direct learning model show the same learning achievement. On students with medium level of creativity, guided discovery, problem based and direct learning model show the same learning achievement. On students with low level of creativity, guided discovery, problem based and direct learning model show the same learning achievement. (4) In guided discovery model, students with high and medium level of creativity show the same learning achievement, however students with high level of creativity have better achievement than students with low level of creativity. Students with medium and low level of creativity show the same learning achievement. Using problem based learning model, students with high, medium and low level of creativity show the same achievement. In direct learning model, the result of the three creativity categories also show the same learning achievement.Keywords: guided discovery model, problem based learning model, creativity